Midterm Experience with the Self-Expandable Venus P-Valve™ for Percutaneous Pulmonary Valve Replacement in Large Right Ventricular Outflow Tracts - Kramer, Peter; Schleiger, Anastasia; Duong, Phuoc; Berger, Felix (Journal of interventional cardiology, 2024)
Background. Preliminary results with the recently certified self-expandable Venus P-Valve™ designed for percutaneous pulmonary valve implantation in patients with dilated right ventricular outflow tracts are encouraging, but experience is limited. We therefore assessed our early and midterm outcomes with the Venus P-Valve™. Methods. Twenty patients who underwent Venus P-Valve™ implantation in our institution were included in this retrospective study. Procedural data and clinical, imaging, and hemodynamic data at baseline and last follow-up were recorded and analyzed. Results. Mean patient age was 35.0 ± 16.8 years, and five patients were <18 years of age. Procedural success was 100%, and there was no major valve-related procedural complication. At last follow-up (median 0.5 (range 0.1–6.6) years), valve function was excellent in all patients. Two patients had mild regurgitation after 6.2 and 6.6 years, respectively, while all other patients had no or only trace regurgitation. Flow was unobstructed with a mean gradient estimated by echocardiography of 12 ± 4 mmHg. NYHA functional class improved significantly (p=0.009), and right ventricular dimensions significantly decreased (right ventricular end-diastolic diameter 56±9 mm vs. 44±8 mm) (p<0.001). Transient benign ventricular arrhythmias were frequent. One patient experienced a severe arrhythmia with sustained ventricular tachycardia during follow-up. Conclusions. Early and midterm results with the Venus P-Valve™ are excellent. It considerably extends the interventional options and offers a safe and effective alternative to surgery in patients with large right ventricular outflow tracts. Larger multi-institutional studies with longer follow-up duration are required to reliably assess the long-term performance and possible long-term complications of the Venus P-Valve™.